'Standing accused': analogy and dialogue as the personhood of substance - Lee, Eric Austin (2013)
This thesis engages the issue of personhood, arguing that persons are both analogical and dialogical beings. I look at personhood first, from the standpoint of the slandered and 'accused' person. Beginning with the scene of Christ before Pilate, I show that the logic of accusation is unassailably couched within the grammar of testimony or of bearing witness (Chapter 1). Next, I treat the Dreyfus Affair and the contrast of mystique and politique in the writings of Charles Peguy (Chapter 2). Here I tum to the 'accusation in the accusative' logic of Emmanuel Levinas, demonstrating that within an approach of radical alterity to the exclusion of other grammatico-ontological cases, the person becomes lost without some sort of original, analogical case of 'giving' (Chapter 3). In response to extreme accounts slander and of the heterogeneity of the person, this thesis, secondly, proposes that the person should be understood first analogically, and secondly, as an analogical extension, dialogically. To this end I examine the debate concerning analogy in Thomas Aquinas and the tradition that followed him. I explore both the metaphysical path of resolutio, perfection, and theological recapitulation (Chapter 4), and then look to the debate on analogy itself arguing that it is best understood as pointing toward an analogia entis that is coextensively an analogia personae (Chapter 5). Finally, I conclude with an articulation of the person as dialogical. I look first to the form of dialogue in Plato, then I conclude with three sections enacting a 'call and response' of the divine persons speaking 'to the creature through the creature', where I end with an account of persons living a dialogically ensouled life within the communio personarum (Chapter 6). I finish with a brief conclusion recapitulating the argument with a Christie entreaty toward the neighbor.